Fourth Swiss Annual Meeting on HER2-Positive Breast Cancer: Antibody-Drug Conjugates in HER2-Positive Disease and Beyond - Marcus Vetter; Christian Kurzeder (healthbook TIMES. Oncology Hematology, 2025)
The development of antibody-based therapies has transformed the treatment of human epidermal growth factor receptor 2 (HER2)-positive breast cancer. More recently, HER2-directed antibody-drug conjugates (ADCs) have demonstrated efficacy in HER2-negative breast cancer patients who had a certain level of HER2 expression (HER2 low). The 4th Swiss Annual Meeting on HER2-positive breast cancer held in Basel, Switzerland, on April 11, 2025, brought together leading experts in the field of oncology to discuss the latest advancements and challenges in this clinical setting. Prof. Dr Michael Untch, Helios Hospital Berlin-Buch, Germany, presented a comprehensive overview of practice-changing data and future directions. PD Dr Marcus Vetter, Cantonal Hospital Baselland, Switzerland, discussed emerging therapies for HER2-low and triple-negative breast cancer (TNBC) with a focus on ADCs as well as therapy sequencing. Prof. Dr Hervé Bonnefoi, Bordeaux Institute of Oncology, France, highlighted the importance of therapy optimization in early HER2-positive breast cancer and TNBC. PD Dr Khalil Zaman, Lausanne University Hospital, Switzerland, addressed the topic of resistance to ADC therapy. Prof. Dr Christian Kurzeder, University Hospital Basel, Switzerland, discussed treatment-associated toxicities that require close and proactive monitoring. This review summarizes the key messages from the meeting.